MENGURAI RAHASIA NILAI PERUSAHAAN: PERAN STRUKTUR MODAL, KEBIJAKAN DIVIDEN, DAN PERTUMBUHAN PENJUALAN - Dendi Purnama; Amir Hamzah (Jurnal Bina Bangsa Ekonomika, 2023)
This study aims to determine the effect of capital structure, dividend policy and sales growth on company value. This study used descriptive and verifiative methods. The population in this study is 25 mining sub-sector companies listed on the Indonesia Stock Exchange for the period 2017 to 2022. The sampling technique used is a purposive sampling technique with a sample of 23 companies from the period 2017 to 2022 as many as 138 observational data. The analysis technique uses panel data regression using the Eviews analysis tool. The results showed that capital structure negatively affects company value, dividend policy and sales growth have a significant positive effect on company value. The implications in this study provide useful insights for company management in making smarter and directed financial and operational decisions towards increasing company value